Pengaruh Kemiskinan, Indeks Pembangunan Manusia, dan Pertumbuhan Ekonomi terhadap Indeks Pembangunan Ketenagakerjaan di Indonesia - Berta, Helira Elma; Maryati, Sri; Ariyanto, Edi (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This study examines the effects of poverty, the Human Development Index, and economic growth on the Labor Development Index across Indonesian provinces during 2020-2024. The issue is important because labor development reflects not only employment opportunities, but also labor quality, productivity, welfare, protection, and regional institutional capacity. The study uses balanced panel data consisting of 34 provinces over five years, producing 170 observations. The dependent variable is the Labor Development Index, while the independent variables are the poverty rate, the Human Development Index, and economic growth measured by the growth rate of gross regional domestic product. Data are analyzed using panel regression in Stata through pooled ordinary least squares, fixed effect, and random effect models. The individual effect test, Breusch-Pagan Lagrange multiplier test, and Hausman test indicate that the Fixed Effect model is the most appropriate specification. The final estimation uses Cluster-Robust standard errors at the provincial level. The results show that the Human Development Index and economic growth have positive and statistically significant effects on the Labor Development Index, whereas poverty has a positive but statistically insignificant coefficient. These findings imply that improving labor development requires more than reducing poverty. It also needs stronger human development and inclusive regional economic growth that can create productive and decent work.